The degradation of organic compounds impacts the crystallization of clay minerals and vice versa - Jacquemot, Pierre (Sci Rep, 2019)
Expanding our capabilities to unambiguously identify ancient traces of life in ancient rocks requires laboratory experiments to better constrain the evolution of biomolecules during advanced fossilization processes. Here, we submitted RNA to hydrothermal conditions in the presence of a gel of Al-smectite stoichiometry at 200 °C for 20 days. NMR and STXM-XANES investigations revealed that the organic fraction of the residues is no longer RNA, nor the quite homogeneous aromatic-rich residue obtained in the absence of clays, but rather consists of particles of various chemical composition including amide-rich compounds. Rather than the pure clays obtained in the absence of RNA, electron microscopy (SEM and TEM) and diffraction (XRD) data showed that the mineralogy of the experimental residues includes amorphous silica and aluminosilicates mixed together with nanoscales phosphates and clay minerals. In addition to the influence of clay minerals on the degradation of organic compounds, these results evidence the influence of the presence of organic compounds on the nature of the mineral assemblage, highlighting the importance of fine-scale mineralogical investigations when discussing the nature/origin of organo-mineral microstructures found in ancient rocks.